Role of fungal-mediated mineralization in biocementation of sand and its improved compressive strength. (September 2018) - Fang, Chaolin; Kumari, Deepika; Zhu, Xuejiao; Achal, Varenyam
Abstract: The process of microbially induced calcite precipitation (MICP) is widely used recently in construction engineering in improving compressive strength, durability and self-healing of building materials and culture heritages. However, most of researches to date have concentrated on prokaryotic systems despite of associated limitation of urease-positive bacteria in biocementation. In the present study, we exploited the role of one urease-positive fungal strain Penicillium chrysogenum CS1 for the first time in biocementation of sand in column to produce sandstone of significant compressive strength. Further, the research provided understanding of the involved mechanisms and advantages of fungal-mediated production of calcite in cementing sand granules over same process using bacteria. Highlights: First report on role of fungi in calcite precipitation leading to cementation in sand column. Fungal-mediated calcite precipitation formed sandstone of significant compressive strength. Characteristic appearance of precipitate was observed by SEM, and evaluated by FTIR and XRD.